Identification of Immune-Related Hub Genes in Parkinson’s Disease - Chen, Lin; Wang, Yong; Huang, Juan; Hu, Binbin; Huang, Wei (Frontiers in Genetics, 2022)
Background: Parkinson’s disease (PD) is a common, age-related and progressive neurodegenerative disease. Growing evidence supports that immune dysfunction plays an essential role in the pathogenic process of PD. The objective of this study was to explore potential immune-related hub genes and immune infiltration patterns of PD. Method: Microarray expression data of human postmortem substantia nigra samples from GSE7621, GSE20141 and GSE49036. Key module genes screened via WGCNA and immune-related genes were intersected to obtain immune-key genes. Functional enrichment analysis was performed on immune-key genes of PD. Meanwhile, immune infiltration analysis was applied by ssGSEA algorithm to detect differential immune cell types in substantia nigra between PD samples and the control samples. LASSO analysis was performed to further find out immune-related hub genes for PD. ROC curve analysis was used to evaluate the diagnostic value of the immune-related hub genes. The correlations between immune-related hub genes and differential immune cell types were assessed. Result: Our findings indicated that 4 hub genes (SLC18A2, L1CAM, S100A12, CXCR4) and 5 immune cell types (neutrophil, T follicular helper cell, MDSC, type 1 helper cell, immature B cell, immature dendritic cell and CD56 bright natural killer cell) were identified. The diagnostic model of 4 hub genes was constructed. The AUC value of the four-gene-combined was 0.92. The AUC value of each immune-related hub gene (SLC18A2, L1CAM, S100A12, CXCR4) was 0.81, 0.78, 0.78 and 0.76, respectively. Conclusion: In conclusion, SLC18A2, L1CAM, S100A12 and CXCR4 were identified as potential biomarkers for the pathogenesis of PD, which should be further explored in the future for PD.